Effects of thyroxine on adhesion molecules and proinflammatory cytokines secretion on human umbilical vein endothelial cells - Attabak Milani; Mohammad Hassan Khadem-Ansari; Yousef Rasmi (Wolters Kluwer Medknow Publications, 2019)
Thyroid dysfunction is associated with elevated cardiovascular risk factors and atherosclerosis. It could be suggested that, hyperthyroidism is related to a higher prevalence of arterial abnormalities. Therefore, evaluating the endothelial dysfunction (ED) related biomarkers seem to be an important issue. It is not clear whether endothelial cells are biologically responsive to thyroid hormones (THs) or how THs induces the production of endothelial cells (EC)-derived proinflammatory mediators. Hence, in this study the effects of thyroxine (T4) on ED and inflammatory related mediators were evaluated. Human umbilical vein endothelial cells was used as endothelial cell model which was treated with concentrations of 50, 100, 200 nmol/L of T4 in various exposure times. In the following, gene and protein expression levels of EC-related markers including intercellular adhesion molecule-1 (ICAM-1), vascular endothelial growth factor (VEGF), and E-selectin were determined using real time polymerase chain reaction (RT-PCR) and western blotting methods. Also, interleukin-6 (IL-6) and tumor necrosis factor (TNF-α) protein levels as proinflammatory cytokines were determined by enzyme linked immunosorbent assay (ELISA) method. Gene and protein expression analysis revealed that T4 treatments up regulated the levels of VEGF, ICAM-1, and E-selectin as ED markers. In addition, T4-treated cells had higher significant levels of IL-6 and TNF-α versus untreated cells in different incubation times. This study proposed the atherosclerotic effects of thyroid hormone. Based on our findings, T4 had strong effects on the gene and protein expression levels of pro-inflammatory, angiogenesis, and ED major mediators associated with atherosclerosis development.